Generalized Rough \((m, n)\) Bi-\(Γ\)-ideals in Ordered LA-\(Γ\)-Semigroups - Ansari, Moin Akhtar; Iampan, Aiyared (Communications in Mathematics and Applications, 2021)
In this paper, generalized rough \((m,n)\)-(bi-ideals, quasi-ideals and interior ideals) have been introduced in ordered LA-\(Γ\)-semigroups by means of pseudo order of relations. Some combined results have been proved. Properties of rough m-left \(Γ\)-ideals, n-right \(Γ\)-ideals rough interior \((m,n)\)-\(Γ\)-ideals, rough \((m,n)\)-quasi-\(Γ\)-ideals and rough \((m,n)\) bi-\(Γ\)-ideals in ordered LA-\(Γ\)-Semigroups have been studied and discussed by using pseudo order of relations.